Song learning within group music therapy in combination with Picture Communication Symbols (PCS) for children diagnosed with Autism Spectrum Disorder (ASD) - Lotter, Carol Barbara (University of Pretoria, 2017)
Mini Dissertation (MMus)--University of Pretoria, 2017.